O problemie ochrony niemieckich praw własności intelektualnej w Polsce w pierwszych latach po II wojnie światowej - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Right after the end of the Second World War a decision was taken to deal with the problem of patent rights and copyright of German nationals by means of internal (national) regulations. A relevant letter was sent in April 1946 to the Ministry of Reconstruction by the Construction Research Institute. This began a rather lively exchange of correspondence on the ministerial level. Particularly active in it were three ministries: Ministry of Reconstruction, Ministry of Justice and Minister of Foreign Aff airs. In the end, however, the problem of the use of patents belonging to German nationals under pre-war international agreements was resolved by means of the London Accord of 27 July 1946 which Poland endorsed in late 1946. What turned to be much more problematic was the regulation of German copyright. The Polish authorities were considering the adoption of the so-called decree on partial revocation of copyright on technical and scientifi c works by German authors. However, owing to a lack of consent from the various ministries as well as uncertainty about possible future consequences associated with compensation the attempts proved ineff ective.
Keywords: własność intelektualna; prawo autorskie do patentów; prawa autorskie i prawa patentowe obywateli niemieckich po drugiej wojnie światowej